The answer is: " x – (x + 8) " .
{Note: The simplified form is: " -8 ."}.
_______
Explanation:
We are given:
→ " A number decreased by the sum of the number and eight."
_______
Let "x" represent the number referred to as "a number."
_______
"{A number} decreased by {the sum of the (number and eight).}" ;
↑ ↑ ↑
"x" "(minus)" " (x + 8) " ;
_______
So; we can write this as:
_______
→ " x – (x + 8) " ;
_______
Edit—Addendum:
{Now, if are then asked to simply this expression}:
→ " x – (x + 8) " ;
_______
Then: Rewrite as:
→ " x – 1(x + 8) " ;
_______
Take note of the distributive property of multiplication:
→ " a(b + c) = ab + ac " ;
_______
Likewise:
→ " x – 1(x + 8) " ;
→ Note the: " -1(x + 8) ";
_______
→ -1(x + 8) = (-1*x) + (-1*8) ;
= (-1x) + (-8) ;
= (-1x – 8) ;
Now, bring down the " ⁺x " :
→ " x – 1x – 8 " ;
Rewrite as:
→ " 1x – 1x – 8 " ;
Simplify:
→ " 1x – 1x – 8 " ;
= " (1x – 1x) – 8 " ;
= " (0 – 8) " ;
= " -8 " ; which is the simplified form of the
given algebraic expression.
_______
Hope this explanation is helpful to you!
________